Analisis Pemanfaatan Teknologi Berbasis Artificial Intelligence (AI) dalam Layanan Keuangan Syariah bagi Mahasiswa UIN Raden Mas Said Surakarta - Fery Indra Kurniawan; Dicky Pratama; Hafidh Abdullah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the perceptions and acceptance levels of students at UIN Raden Mas Said Surakarta towards the use of Artificial Intelligence (AI) technology in Islamic financial services. This study uses a qualitative approach with the Technology Acceptance Model (TAM) theoretical framework, which emphasizes the dimensions of perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use. Data were obtained through in-depth interviews with twelve students from various Islamic economics and business study programs. The results show that the majority of respondents have a positive view of the use of AI in Islamic finance. They believe that AI can improve the efficiency, accuracy, and personalization of financial services, as well as help ensure compliance with Islamic principles. However, there are concerns regarding data security, privacy, potential algorithmic bias, and the reduced role of humans in the decision-making process. In general, students expressed high interest in using AI-based Islamic financial services in the future, provided that security, transparency, and strict Islamic oversight are guaranteed. This study confirms that the younger generation of Muslims has the potential to become active users and guardians of ethical values in the digital transformation of Islamic finance.